2012
DOI: 10.1371/journal.pone.0048619
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair and Cell Cycle Biomarkers of Radiation Exposure and Inflammation Stress in Human Blood

Abstract: DNA damage and repair are hallmarks of cellular responses to ionizing radiation. We hypothesized that monitoring the expression of DNA repair-associated genes would enhance the detection of individuals exposed to radiation versus other forms of physiological stress. We employed the human blood ex vivo radiation model to investigate the expression responses of DNA repair genes in repeated blood samples from healthy, non-smoking men and women exposed to 2 Gy of X-rays in the context of inflammation stress mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 45 publications
5
63
0
Order By: Relevance
“…For example, a previous study of human blood samples observed greater than twofold changes in the expression of genes involved in specific DNA repair functions (XPC, DDB2, LIGI, POLH, and RAD51) at 24 h after exposure to 2 Gy of X-rays. 18 Furthermore, two DNA damage response molecules, γ-H2AX and pChk2, were found to be expressed at approximately 0.1-48 and 0.25-32 h, respectively, after exposure to ionizing radiation from intraoral dental radiographs. 19 Therefore, it would be reasonable not to detect DSBs at 24 h after exposure.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a previous study of human blood samples observed greater than twofold changes in the expression of genes involved in specific DNA repair functions (XPC, DDB2, LIGI, POLH, and RAD51) at 24 h after exposure to 2 Gy of X-rays. 18 Furthermore, two DNA damage response molecules, γ-H2AX and pChk2, were found to be expressed at approximately 0.1-48 and 0.25-32 h, respectively, after exposure to ionizing radiation from intraoral dental radiographs. 19 Therefore, it would be reasonable not to detect DSBs at 24 h after exposure.…”
Section: Discussionmentioning
confidence: 96%
“…Damage to DNA integrity is critical and elicits a global stress response that is characterized by activation of an array of signaling pathways. Genes and proteins implicated in DNA repair, cell cycle checkpoints, apoptosis and changes in gene expression are modulated in a dose-dependent manner by ionizing radiation (Amundson and Fornace, 2001;Budworth et al, 2012;Chaudhry et al, 2012;de Toledo et al, 1998). Several reports have demonstrated that activated microglia play a critical role in IR induced impairment of hippocampal neurogenesis (Monje et al, 2002;Monje et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…They have also been used to identify genetic determinants of pathways involved in the cytotoxic response to IR (Shukla and Dolan 2005, Hartford and Dolan 2007, Niu et al 2010). Recently, peripheral blood mononuclear cells (PBMC) isolated from a small panel of healthy volunteers were also used to identify genes associated with radiation response (Budworth et al 2012). It remains unclear, however, whether immortalized cell lines are appropriate surrogates for primary cells isolated from individuals and accurately reflect the response and the pathways involved in normal cells.…”
Section: Introductionmentioning
confidence: 99%